Exploring Traditional uses, phytochemistry, pharmacology and future prospectives of Santalum album - Agarwal, Shashank; Arif, Rizwan; Kumar Joshi, Santosh; Jahan, Ishrat; Anurag, Anurag; Sharma, Alok; Dhoke, Shrikant (Journal of Neonatal Surgery, 2025)
One of the rarest and most precious natural smell sources, Indian sandalwood, or Santalum album L. (Santalaceae), has substantial industrial and medicinal use. For the past 250 years. S album is a popular option all over the world since it is cultivated in India and its fragrant oil is well-known for both its medicinal qualities and sweetness.Many ancient medicinal systems have employed sandalwood and the essential oil derived from sandal heartwood to cure and prevent a wide range of ailments, including Ayurveda, Unani, and Siddha medicine.Due to its abundance of phytochemicals, especially sesquiterpenes, Sandalwood has a wide range of medicinal and medical uses. A comprehensive bibliographic analysis was conducted by examining internationally known books, index- and non-indexed journals, and widely used scientific databases [Pub Med, Sci-Hub,SciFinder, Scopus, ACS, and Web of Science]. Numerous pharmacological properties, from antibacterial to anticancer, have been shown in contemporary pharmacological investigations. Sandalwood oil and its components have not shown any appreciable toxicity; however, more Study on the chemical components and how they exhibit specific biological activities is required to fully comprehend the phytochemical composition and the intricate pharmacological impact of this plant. The poor productivity of this endangered plant and its rising commercial exploitation have sparked concerns about how to conserve it and increase its output using contemporary equipment and methods. The review covers the traditional use, phytochemistry, pharmacology, distillation, and biological activities of Sandalwood to reveal its value for industry and medicine as well as any Study gaps that need to be filled.